Hypokalaemia induces Ca2+ overload and Ca2+ waves in ventricular myocytes by reducing Na+, K+‐ATPase α2 activity. (11th November 2014) - Aronsen, J. M.; Skogestad, J.; Lewalle, A.; Louch, W. E.; Hougen, K.; Stokke, M. K.; Swift, F.; Niederer, S.; Smith, N. P.; Sejersted, O. M.; Sjaastad, I.
Abstract : Key points: Hypokalaemia is a risk factor for development of ventricular arrhythmias. In rat ventricular myocytes, low extracellular K + (corresponding to clinical moderate hypokalaemia) increased Ca 2+ wave probability, Ca 2+ transient amplitude, sarcoplasmic reticulum (SR) Ca 2+ load and induced SR Ca 2+ leak. Low extracellular K + reduced Na +, K + ‐ATPase (NKA) activity and hyperpolarized the resting membrane potential in ventricular myocytes. Both experimental data and modelling indicate that reduced NKA activity and subsequent Na + accumulation sensed by the Na +, Ca 2+ exchanger (NCX) lead to increased Ca 2+ transient amplitude despite concomitant hyperpolarization of the resting membrane potential. Low extracellular K + induced Ca 2+ overload by lowering NKA α2 activity. Triggered ventricular arrhythmias in patients with hypokalaemia may therefore be attributed to reduced NCX forward mode activity linked to an effect on the NKA α2 isoform. Abstract: Hypokalaemia is a risk factor for development of ventricular arrhythmias. The aim of this study was to determine the cellular mechanisms leading to triggering of arrhythmias in ventricular myocytes exposed to low Ko . Low Ko, corresponding to moderate hypokalaemia, increased Ca 2+ transient amplitude, sarcoplasmic reticulum (SR) Ca 2+ load, SR Ca 2+ leak and Ca 2+ wave probability in field stimulated rat ventricular myocytes. The mechanisms leading to Ca 2+ overload were examined. Low Ko reduced Na +, K + ‐ATPase (NKA) currents, increased cytosolic Na + concentration and increased the Na + level sensed by the Na +, Ca 2+ exchanger (NCX). Low Ko also hyperpolarized the resting membrane potential (RMP) without significant alterations in action potential duration. Experiments in voltage clamped and field stimulated ventricular myocytes, along with mathematical modelling, suggested that low Ko increases the Ca 2+ transient amplitude by reducing NKA activity despite hyperpolarization of the RMP. Selective inhibition of the NKA α2 isoform by low dose ouabain abolished the ability of low Ko to reduce NKA currents, to increase Na + levels sensed by NCX and to increase the Ca 2+ transient amplitude. We conclude that low Ko, within the range of moderate hypokalaemia, increases Ca 2+ levels in ventricular myocytes by reducing the pumping rate of the NKA α2 isoform with subsequent Na + accumulation sensed by the NCX. These data highlight reduced NKA α2 ‐mediated control of NCX activity as a possible mechanism underlying triggered ventricular arrhythmias in patients with hypokalaemia.